2009
DOI: 10.1007/s11832-009-0201-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a vertical expandable prosthetic titanium rib on shoulder balance in patients with congenital scoliosis

Abstract: Purpose To evaluate the effect of a vertical expandable prosthetic titanium rib (VEPTR) on shoulder balance in patients with congenital scoliosis. Methods Fifteen patients had a thoracic congenital scoliosis. The Cobb angles of the thoracic primary curves were measured. Preoperative measurements of the coracoid height difference (CHD; expressed in millimeters) and the clavicular tilt angle difference (CTAD; expressed in degrees) were performed for all patients. All of the patients were treated with VEPTR open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…He wrote, "Arthrodesis in situ is the optimal form of early prophylactic surgical treatment for congenital scoliosis caused by a unilateral failure of vertebral segmentation. [13][14][15][16][17][18][19][20][21][22][23] In an effort to better define the indications and outcomes of nonsyndromic patients treated with VEPTR, we report multicenter data with midterm follow-up. The abnormal spine is not contributing to vertical height, and it is only making the spine more crooked."…”
Section: Discussionmentioning
confidence: 99%
“…He wrote, "Arthrodesis in situ is the optimal form of early prophylactic surgical treatment for congenital scoliosis caused by a unilateral failure of vertebral segmentation. [13][14][15][16][17][18][19][20][21][22][23] In an effort to better define the indications and outcomes of nonsyndromic patients treated with VEPTR, we report multicenter data with midterm follow-up. The abnormal spine is not contributing to vertical height, and it is only making the spine more crooked."…”
Section: Discussionmentioning
confidence: 99%
“…Wound dehiscence or superficial wound infection may lead to deep infection involving the implant that may end in a difficult problem most commonly managed at best with removal of the implant as a common outcome. Campbell and others 24,25,29,[32][33][34] have recounted their experience with infection in VEPTR patients. Campbell et al 29 reported an overall incidence of infection of 1.9% per surgical procedure.…”
Section: Complications In Veptr and Rib-based Distraction Devicesmentioning
confidence: 99%
“…4 In addition, growing rod technique is supposed to provide a stable construct covering the shortest possible segments to maintain correction in all planes. 7 In this study, distracting the rods using either concave side as in single rod or both sides as in dual rods improved the major curve magnitudes and shoulder balance similarly. Thus, gradual correction of Cobb angle may be supposed to be amenable of the restoration of shoulder balance as it is put forward in vertical expandable prosthetic titanium rib (VEPTR) intervention for congenital curves.…”
Section: Discussionmentioning
confidence: 58%
“…5 Establishment of shoulder balance, as a part of cosmesis, is one of the most important measures of success in scoliosis surgery because of its effect on patient appearance and satisfaction. 7 In this young patient group, growing rods without fusion are used to arrest progression of the deformity to delay the definitive spinal fusion and segmental spinal instrumentation until there exist no growth remaining to maintain trunk balance and allow spinal growth. 7 In this young patient group, growing rods without fusion are used to arrest progression of the deformity to delay the definitive spinal fusion and segmental spinal instrumentation until there exist no growth remaining to maintain trunk balance and allow spinal growth.…”
Section: Discussionmentioning
confidence: 99%